An Encomium for Community College Students in Five Scenes - James Gallagher (Journal of the Assembly for Expanded Perspectives on Learning, 2022)
Books start arriving at my apartment by the boxful. As part of the committee judging the CCCC Outstanding Book Contest, I am inundated with books, and I am excited to get down to reading them. I feel like a graduate student all over again, reading things I would never read if I weren’t “made” to (New Materialisms, anyone?). Most of the books excite me and make me think about how I can move forward as a teacher of first year writing. Some of them hurt my brain. Some of them annoy me.
Keywords: JAEPL